2016
DOI: 10.2147/cia.s110532
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of unknown and untreated arrhythmias in an older outpatient population screened by wireless long-term recording ECG

Abstract: PurposeWith longer life expectancies, the prevalence of arrhythmias is increasing; thus, there is a need for new methods to screen the older outpatient population. This population-based study describes the prevalence of arrhythmias in 200 outpatients aged ≥66 years. We also investigated the feasibility of wireless long-term recording (LTR) using the ECG-BodyKom®.MethodsTwo hundred elderly persons aged 66–93 years were recruited from the Swedish National Study on Aging and Care in 2010–2013, and data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
8
0
3
Order By: Relevance
“…los sujetos mayores de esta edad, en 14% en 85 años y en 27% de pacientes hospitalizados o institucionalizados mayores de 90 años (8,9) . La prevalencia de contracciones ectópicas ventriculares varía del 76% en los estudios realizados con ECG basal al 96% en los estudios realizados con ECG de monitorización portátil.…”
Section: Del Nacionalunclassified
See 2 more Smart Citations
“…los sujetos mayores de esta edad, en 14% en 85 años y en 27% de pacientes hospitalizados o institucionalizados mayores de 90 años (8,9) . La prevalencia de contracciones ectópicas ventriculares varía del 76% en los estudios realizados con ECG basal al 96% en los estudios realizados con ECG de monitorización portátil.…”
Section: Del Nacionalunclassified
“…En pacientes con más de 65 años, la fibrilación auricular se observa en el 4,8% de las mujeres y el 6,2% de los hombres. Estas diferencias de sexo puede estar relacionado con el estilo de vida y un mayor consumo de tabaco y alcohol en hombres que en mujeres, además de otras variables fisiológicas (4,9) . En sujetos centenarios (≥100 años) se encuentran anormalidades del ECG en más del 95% de los casos.…”
Section: Del Nacionalunclassified
See 1 more Smart Citation
“…Recent data have underlined that a better screening for atrial fibrillation discloses unknown arrhythmias not only in patients over 80 years but also in younger patients, aged 66 to 80 years. 4 Hence, the prescription of NOACs is expected to increase significantly in patients who are still concerned with FIT.…”
Section: Fecal Immunochemical Testing For Colorectal Cancer and Medicmentioning
confidence: 99%
“…2 The FNA procedure is not the preferred modality for tissue diagnosis because of the inability to obtain tissue architecture, 3 but historically EUS-guided core biopsy specimens have been technically difficult to obtain. In the accompanying editorial, 4 it is suggested that newer, more flexible EUS core biopsy needles may become the preferred tissue sampling device. We describe 2 recent cases of AIP in which tissue was obtained with a new EUS-guided core biopsy needle, to demonstrate the ability to obtain samples with preserved architecture.…”
Section: Diagnosis Of Autoimmune Pancreatitis Using New Flexible Eusmentioning
confidence: 99%